Characterisation of enzyme catalysed hydrolysation stage of poly(lactic acid) fibre surface by nanoscale thermal analysis: New mechanistic insight. (July 2022) - Nguyen, Huong Lan; Bechtold, Thomas; Fabbri, Filippo; Pellis, Alessandro; Guebitz, Georg M.; Pham, Tung
Graphical abstract: Highlights: Enzyme catalysed hydrolysis of fibre surface is monitored by nanoscale thermal analysis. Amorphous surface region is selectively hydrolysed due to limited access of enzyme to fibre core. Defined bio-based fibres with highly crystalline surface is designed by environmentally friendly white biotech process. Abstract: Enzyme catalysed hydrolysis of bio-based poly(lactic acid) (PLA) represents an environmentally-friendly route for a controlled modification of polymer fibres. In this work, the topochemical hydrolysis reaction of cutinase from Humicola insolens (HiC) on PLA fibre was mechanistically investigated using the advanced surface sensitive nanoscale thermal analysis (nano-TA) technique. The enzymatic hydrolysis preferentially occurs at the amorphous regions of the fibre outer layer, thus leading to randomised hydrolysis, monomer release and ablation of the fibre surface during the initial phase of the hydrolysis. Due to the higher hydrolysis rate at amorphous regions, the crystallinity of the fibre outer layer increases. As a result, an enrichment in overall fibre crystallinity is observed by increased melting enthalpy. The accessibility of the enzyme to the fibre core is restricted, thus the change in crystallinity is prevalent on the fibre outer region. The observed increase of the surface softening temperature from the glass transition temperature close to the melting on-set of crystalline PLA as detected by nano-TA supports the hypothesis, that selective hydrolysis preferably takes place at the amorphous region at the fibre outer layer, thus leading to modified PLA fibres with an unchanged fibre core and a very thin and highly crystalline surface layer.